Treatment, outcome and quality of life of 1239 patients with advanced non-small cell lung cancer – final results from the prospective German TLK cohort study. (October 2017) - von Verschuer, Ulla; Schnell, Roland; Tessen, Hans Werner; Eggert, Jochen; Binninger, Adrian; Spring, Lisa; Jänicke, Martina; Marschner, Norbert; ,
Highlights: Real-life data on the treatment of 1239 patients with advanced NSCLC in Germany. Carboplatin versus cisplatin: similar overall survival (mOS 12 months) and HRQOL. Outcome in routine care was comparable to outcome in randomized clinical trials. The symptoms fatigue, nausea, dyspnoea and pain need special attention. Patients treated with TKIs had superior outcome and HRQOL. Abstract: Objectives: Real-life data on advanced non-small cell lung cancer (NSCLC) are centrally important to complement the results from clinical trials and to improve the standard of care. We present data on the choice of systemic first- and second-line treatment, number of treatment lines, survival and longitudinal data on health-related quality of life (HRQOL) of patients treated by medical oncologists in Germany. Materials and methods: 1239 patients with advanced NSCLC were recruited at start of first-line therapy into the prospective German clinical cohort study TLK (Tumour Registry Lung Cancer) by 107 sites between February 2010 and December 2013 and followed-up until January 2016. HRQOL was assessed using the EORTC QLQ-C30 and LC13 questionnaires. Results: Most patients receive carboplatin- or cisplatin-based doublet chemotherapy in first-line treatment. The choice of platinum agent did neither influence the outcome: median overall survival (OS) was 12.2 months for carboplatin combinations (95% confidence interval [CI] 10.0–13.8) and 11.9 months for cisplatin combinations (95% CI 10.2–13.8), nor did it have a marked impact on the HRQOL. Patients receiving cisplatin were younger and fitter at start of therapy than patients receiving carboplatin or mono-chemotherapy. The longitudinal HRQOL analysis revealed the main symptoms that need to be addressed in follow-up care, irrespective of the platinum agent: fatigue, nausea, dyspnoea and pain. The patients receiving targeted therapies with tyrosine kinase inhibitors (TKIs) had a median OS of 22.1 months (95% CI 15.0–35.1) and considerably superior HRQOL. Conclusion: There was no difference in outcome between the platinum compounds cisplatin and carboplatin in first-line treatment of advanced NSCLC in routine care. This is the first report of longitudinal HRQOL data comparing treatments, showing no difference between carboplatin and cisplatin.